2019
DOI: 10.1186/s12886-019-1229-4
|View full text |Cite
|
Sign up to set email alerts
|

The effects of c-Src kinase on EMT signaling pathway in human lens epithelial cells associated with lens diseases

Abstract: Background: The signaling pathway of epithelial to mesenchymal transition (EMT) is regulated by c-Src kinase in many cells. The purpose of this study was to investigate the effects of c-Src kinase on EMT of human lens epithelial cells in vivo stimulated by different factors. Methods: Human lens epithelial cells, HLE-B3, were exposed to either an inflammatory factor, specifically IL-1α, IL-6, TNF-α or IL-1β, at 10 ng/mL or high glucose (35.5 mM) for 30 mins. Activity of c-Src kinase was evaluated by the express… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…Previous studies described the importance of the Src kinase pathway for EMT in colorectal cancer 33 and lens diseases; 34 Src phosphorylation was the assay indicator. Therefore, we examined the phosphorylation level of Src in CMECs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies described the importance of the Src kinase pathway for EMT in colorectal cancer 33 and lens diseases; 34 Src phosphorylation was the assay indicator. Therefore, we examined the phosphorylation level of Src in CMECs.…”
Section: Resultsmentioning
confidence: 99%
“…16 Previous studies have shown that c-Src participates in EMT/EndMT of multiple cells. 16,[32][33][34] It is well known that GRP78 is existed in ER, which binds with PERK, IRE1 and ATF6. This comprehensive ER stress inhibition effect is also the advantage of natural active ingredients over specific small molecule inhibitors because even small molecule inhibitors have strong inhibition effect on a specific protein, UPR reaction can be activated by other ways.…”
Section: Discussionmentioning
confidence: 99%
“…VIM is also present in mesenchymal cells and different stages of cell development 93 . In vitro and in vivo criteria for type II EMT transition to fibroblasts include increased expression of VIM 94 , among others, and such changes have been studied in lens epithelium 95,96 . In vitro models for PCO have found LECs capable of proliferating and migrating on the IOL-LC complex's posterior capsule to be rich in VIM and actin 11 .…”
Section: Tgfβ Signaling May Be the Most Accountable For Long-term Myomentioning
confidence: 99%
“…Epithelial-mesenchymal transition (EMT) involves loss of the epithelial characteristics of epithelial cells and acquisition of mesenchymal characteristics under various external stimuli (Dongre et al 2019). Various studies have shown that LECs undergo EMT under high glucose conditions in vitro or in cataracts of individuals with diabetic mellitus Li et al 2019; Han et al 2018;Du et al 2017). EMT activation leads to disruption of cell-cell junctions and cell polarity, degradation of the basement membrane, and extracellular matrix reorganization, manifested by decreased expression of epithelial markers such as E-cadherin and some kinds of cytokeratin and increased expression of mesenchymal markers such as α-SMA, N-cadherin, vimentin and others (Dongre et al 2019).…”
Section: Introductionmentioning
confidence: 99%